Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect